Entre saberes, sabores e desafios da tarefa educativa com jovens em conflito com a lei: como as educadoras significam os processos educativos do espaço do programa de medidas socioeducativas em meio aberto - Caparrós, Rubia Fernanda Quinelatto (Universidade Federal de São Carlos, 2013)
The study presented in this Master's thesis seeks to bring some insights on the educational work of guiding a program of measures in Socioeducational Half Open, Assisted Freedom and Community Service, in São Carlos / SP, for young people in conflict with the law. The research question guiding the research is explained thus: as the guidelines of the Programme of Measures for Socio Half Open, Probation, in São Carlos / SP, mean the space where they work and how to evaluate educational practices that developed there? To answer the research question, the qualitative research, general aims: to analyze and understand the perspective of the guidelines in relation to their work with young people who are under socio and space in which they operate. Participated as collaborators, six guiding the Programme of Measures for Socio Half Open and were used as instruments interviews, observation records organized in field diaries and document analysis. The data collected were organized and emerged from these four foci of analysis: the Programme of Measures Socioeducational vision of guiding as enabler of new opportunities to the life of (the) young authors (as) an infraction; workshops Socioeducational Measures Program the guiding vision of where they reveal that such workshops constitute integration possibilities, reflection and learning in different areas, the relationship with the school of (the) youth in conflict with the law in guiding vision of showing that (the ) young people are not welcomed by the school, which results in their not stay in that space of formal education, finally, as if guiding and educating young people in conflict with the law in a Programme of Measures Socioeducational announces the live, being together, exchanges and shares offered by the dialogue group. Data analysis is based on Latin American authors and researchers (the) theme, which supported our reflections, to uncover and build paths in social practices that occur within spaces of probation, and announcing the specificity of educational processes that occur in them, may contribute to the (re) integration of young people in conflict with the law to social life.
Between knowledge, flavors and challenges of education task with youth in conflict with the law: how educators mean the educational process of space program in half measures socioeducativas open
Keywords: Educação; Práticas sociais e processos educativos; Educação não formal; Processos educativos em espaço de liberdade vigiada; Educadoras de medida socioeducativa; Programa de Medidas Socioeducativas; Educação não escolar; Processos educativos em espaço de liberdade vigiada; Educadoras de Medida Socioeducativa; Program measures socioeducational; Non-school education; Educational processes in space probation; Educating for Socio Measure; CIENCIAS HUMANAS::EDUCACAO